Assessment of Costs and Environmental Benefits of the Transition from Conventional to Electric Buses in Hanoi - Van Manh, Vu; Quang Vu, Nguyen; Thi Nhat Minh, Doan (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2S, 2025)
Hanoi is facing severe challenges of air pollution and greenhouse-gases emissions from the transportation sector, in which diesel-bus account for a substantial share. In the context of the Government of Viet Nam’s commitment to achieve Net-Zero emissions by 2050, transitioning to a public transport system based on electric buses is an inevitable trend. To assess the sustainability of shifting from conventional internal-combustion engine (ICE) buses to electric buses, this study applies the DPSIR framework in combination with simulation modeling in the eMob Calculator developed by UNEP. The study simulates and compares two scenarios through 2050: i) Maintaining the current share of ICE buses; and ii) Full conversion to electric bus. The results show that the conversion scenario reduces CO₂, fine particulate matter (PM), NOₓ, and energy consumption, while improving long-term operational cost efficiency. Although substantial upfront infrastructure investment is required, the cumulative economic and environmental benefits are evident. The conclusion affirms that transitioning to electric bus is necessary and consistent with national climate goals. The study recommends strengthening financial support, developing charging infrastructure, and designing policy incentives to encourage transport operators to participate in the transition.